Developing a comprehensive framework of community integration for people with acquired brain injury: a conceptual analysis. Issue 14 (3rd July 2019) - Shaikh, Nusratnaaz M.; Kersten, Paula; Siegert, Richard J.; Theadom, Alice
Abstract: Purpose: Despite increasing emphasis on the importance of community integration as an outcome for acquired brain injury (ABI), there is still no consensus on the definition of community integration. The aim of this study was to complete a concept analysis of community integration in people with ABI. Materials and methods: The method of concept clarification was used to guide concept analysis of community integration based on a literature review. Articles were included if they explored community integration in people with ABI. Data extraction was performed by the initial coding of (1) the definition of community integration used in the articles, (2) attributes of community integration recognized in the articles' findings, and (3) the process of community integration. This information was synthesized to develop a model of community integration. Results: Thirty-three articles were identified that met the inclusion criteria. The construct of community integration was found to be a non-linear process reflecting recovery over time, sequential goals, and transitions. Community integration was found to encompass six components including: independence, sense of belonging, adjustment, having a place to live, involved in a meaningful occupational activity, and being socially connected into the community. Antecedents to community integration included individual, injury-related, environmental, and societal factors. Conclusion: The findings of this concept analysis suggest that the concept of community integration is more diverse than previously recognized. New measures and rehabilitation plans capturing all attributes of community integration are needed in clinical practice. Implications for rehabilitation: Understanding of perceptions and lived experiences of people with acquired brain injury through this analysis provides basis to ensure rehabilitation meets patients' needs. This model highlights the need for clinicians to be aware and assess the role of antecedents as well as the attributes of community integration itself to ensure all aspects are addressed in in a manner that will enhance the recovery and improve the level of integration into the community. The finding that community integration is a non-linear process also highlights the need for rehabilitation professionals to review and revise plans over time in response to a person's changing circumstances and recovery journey. This analysis provides the groundwork for an operational model of community integration for the development of a measure of community integration that assesses all six attributes revealed in this review not recognized in previous frameworks.